ATM traffic management in an LMDS wireless access network. - Kuri, J.
We investigate the capacity of LMDS to support ATM services in the local loop. In particular, we evaluate the performance of a MAC protocol for this system when transporting voice and IP traffic using the VBR and GFR service categories of ATM, respectively. Our results show that the MAC protocol is well suited for voice traffic but in general lacks efficient bandwidth management mechanisms to support the more dynamic bandwidth requirements of IP traffic
Keywords: 26 GHz; 28 GHz; ATM services; ATM traffic management; GFR service; IP traffic transport; LMDS wireless access network; MAC protocol simulator; QoS; VBR service; Bandwidth management mechanisms; Buffer management; Dynamic bandwidth requirements; Local loop; Performance evaluation; Voice traffic; Voice transport